Ombudsman Republik Indonesia Sebagai Pengawas Penyelenggaraan Pelayanan Publik Dalam Mewujudkan Good Governance Pada Tahun 2020 - Nayla Magisterani Faatihah; Alifiah Salsabilla Utomo (LP2M, 2022)
This research discusses the performance of supervision carried out by the Ombudsman of the Republic of Indonesia as an agency that provides public services in order to realize good governance in 2020. This study aims to analyze the effectiveness of the performance of the Ombudsman of the Republic of Indonesia whose position is to supervise the implementation of public services in realizing good governance in Indonesia in 2020. In this study, the author used a qualitative method that went through a juridical-normative approach. In collecting the data, the researcher collected data from a wide variety of legal literature, then described according to the focus of this study. This research shows the results that the Ombudsman of the Republic of Indonesia, whose position is to supervise the implementation of public services in realizing good governance, can be said to be quite effective, especially in 2020. This is shown by the realization of the settlement of public complaints against the implementation of public services that have exceeded the target in 2020, which is evidenced by community satisfaction with several indicators such as the speed of service time and the suitability of service products that are considered good by the community. The performance of the Ombudsman of the Republic of Indonesia in realizing good governance is also supported by strengthening the general principles of good governance. Keywords: Ombudsman, Public Services, Good Governance